TEACHERS’ QUESTIONS TO PROMOTE STUDENTS’ CRITICAL THINKING IN EFL CLASS - Noni Agustina; Rini Al Baqoroh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Critical thinking has important role in the EFL class. It can be developed through questioning. However, English teachers are rare to address the critical thinking questions to their students. Therefore, this study aims to investigate to what extent teachers use questions to promote students' critical thinking. This study employed a qualitative approach with open-ended questionnaires and interview to collect data. Seventy-eight of English junior high school teachers in Indonesia were involved in this study. The results of this research revealed that majority teachers employed critical thinking questions. They posed the questions for clarification, assumption, reasons and evidence, viewpoints or perspective, the implication, consequence or alternative, prediction, agreement and disagreement, and summary and conclusion to promote students’ critical thinking skill.